Effects of Exercise Intensity on Microvascular Function in Obese Adolescents - Morrissey, Christopher; Montero, David; Raverdy, Cecile; Masson, Delphine; Amiot, Marie-Jo; Vinet, Agnes (International Journal of Sports Medicine, 2018)
The optimal exercise modality for the improvement of health-related parameters and microvascular function in obese adolescents is not yet fully understood. Therefore, this study aimed to 1) compare the microvascular phenotype of obese and normal-weight adolescents; and 2) to determine the effects of a lifestyle intervention including three months of moderate continuous training (MCT) or high-intensity interval training (HIIT) on health-related parameters and microvascular function in 29 obese adolescents. Body composition, metabolic profile, aerobic fitness and cutaneous blood flow, measured using laser Doppler flowmetry at rest and during post-occlusive reactive hyperemia, were assessed prior to and following lifestyle intervention. Sixteen normal-weight adolescents were included as reference controls for baseline microvascular parameters. At baseline, obese adolescents had higher peak blood flow, peak vascular conductance and area under the curve for post-occlusive reactive hyperemia than normal-weight adolescents. Conversely, peak blood flow, peak vascular conductance and area under the curve data remained unchanged after MCT and HIIT without intergroup differences. However, the peak/basal blood flow ratio decreased in both MCT and HIIT groups without any interaction between groups due to basal CBF increase (tendency p=0.074). Exercise training, whatever the modality, does not improve peak microcirculatory function.
Keywords: exercise training; obesity; microcirculation